2022
DOI: 10.3389/fneur.2022.999536
|View full text |Cite
|
Sign up to set email alerts
|

Association of the stress hyperglycemia ratio and clinical outcomes in patients with stroke: A systematic review and meta-analysis

Abstract: ObjectiveStress hyperglycemia (SH) is common in patients with acute diseases, such as stroke and myocardial infarction. Stress hyperglycemia ratio (SHR) is calculated by glucose/glycated hemoglobin and has been widely used for evaluating SH. But whether SHR is associated with clinical outcomes in stroke patients remains unclear so far. Although many studies have shown that higher SHR means poor outcomes, there is still no absolute evidence that SHR plays a critical role in stroke patients. Hence, we performed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 49 publications
(48 reference statements)
0
16
0
Order By: Relevance
“…SHR, defined as FBG/HbA1c ratio, was used to represent the state of stress hyperglycemia. SHR was associated with functional outcome, complications, HT, and stroke recurrence in AIS patients (9,18,36). Although the pathogenic mechanisms are not so clear, it was proposed that hyperactivated stress could trigger BBB breakdown, oxidative stress response, inflammation and cytokine release in stroke (19).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…SHR, defined as FBG/HbA1c ratio, was used to represent the state of stress hyperglycemia. SHR was associated with functional outcome, complications, HT, and stroke recurrence in AIS patients (9,18,36). Although the pathogenic mechanisms are not so clear, it was proposed that hyperactivated stress could trigger BBB breakdown, oxidative stress response, inflammation and cytokine release in stroke (19).…”
Section: Discussionmentioning
confidence: 95%
“…A number of studies used the stress hyperglycemia ratio (SHR) as a tool to evaluate stress hyperglycemia (15,16). Moreover, many studies have been found that SHR is associated with poor prognosis in AIS patients (17)(18)(19). Recent evidence revealed that elevated SHR was a clinical predictor of stroke-associated pneumonia (9).…”
Section: Introductionmentioning
confidence: 99%
“…Although a range of evidence suggests that stress hyperglycemia is a marker of poor outcomes in patients with AIS ( 14 21 ), this relationship is controversial when stroke severity is considered in further analysis ( 8 ). However, a recent meta-analysis found that stress hyperglycemia could reflect the extent of ischemic damage and lead to poor clinical outcomes in patients with stroke ( 22 ). This finding was consistent with part of our results that stress hyperglycemia is more common in patients with severe stroke, similar to that observed in a previous study ( 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…2) Intervention: mechanical thrombectomy, intravenous thrombolysis, or none of the above. 3) Comparisons: relative low SII vs. relative high SII, and the grouping definition is the same as our previous study ( 12 ). 4) Outcomes: the mRS ≥ 3 points or > 3 points at follow-up was defined as poor outcome, and we categorized stroke severity as NIHSS≥ 5 points.…”
Section: Methodsmentioning
confidence: 99%